The Servant Leadership Analysis and Work Motivation in Determining Organizational Commitment and Employee Performance - Didik Rabuana Artha; I Nengah Suardhika; Nengah Landra (International Journal of Applied Business and International Management, 2023)
Human resources (HR) play an important role and an asset that must be owned by the organization. This is because HR plays an active role in the process of running an organization to achieve goals. Therefore, optimizing the contribution of employees to the company's mission is very important to maintain effective performance. The purpose of this study is to analyze and explain the relationship between servant leadership and work motivation variables with organizational commitment and employee performance at PT. Telkom Access Denpasar. The sample in this study were all permanent employees who worked at several 45 respondents. By using Structural Equation Modeling (SEM) analysis with the help of the Smart-PLS v.3 programs, the results show that the better the implementation of servant leadership can increase employee commitment to the organization. In addition, it was found that employees who are motivated at work will increase their commitment to the organization. The application of servant leadership is not able to, directly and indirectly, determine employee performance. Other results, increasing employee motivation will improve employee performance, either directly or indirectly through the mediation of organizational commitment. Meanwhile, employee commitment was found to have a positive and significant effect on employee performance.